The Effect of Job Satisfaction and Job Insecurity on Employee Turnover Intention - Yusuf, Sulfani; Ferils, Muh.; Hajjad, Mu’fidatul Nurul (Manunggal Halim Jaya, 2023)
The objectives of this study are: 1. To determine the effect of job satisfaction and job insecurity partially on employee turnover intention at PT. Suraco Jaya Abadi Motor Mamuju. 2. To determine the effect of job satisfaction and job insecurity simultaneously on employee turnover intention at PT. Suraco Jaya Abadi Motor Mamuju. This research is a quantitative study with two independent variables and one dependent variable with the test tools to be used, namely 1) validity test, 2) reliability test, 3) multiple linear regression test, t test (partial) and f test (Simultaneous). The sample used in this study was 30 respondents. Research data processing using multiple linear regression with SPSS version 24.0 software tools to read the direction of the influence of the independent variable on the dependent variable partially t test and f test. The results showed that job satisfaction has no influence and is not partially significant on employee turnover intention at PT. Suraco Jaya Abadi Motor Mamuju. Job discomfort has a significant effect partially on employee turnover intention at PT. Suraco Jaya Abadi Motor Mamuju. The results also show that job satisfaction and job insecurity have no influence and are not significant simultaneously on employee turnover intention at PT. Suraco Jaya Abadi Motor Mamuju.